Reducing Implicit Cognitive Biases Through the Performing Arts - García-Arch, Josué; Ventura-Gabarró, Cèlia; Adamuz, Pedro Lorente; Calvo, Pep Gatell; Fuentemilla, Lluís (Frontiers in Psychology, 2021)
The aim of the present research was to test whether involvement in a 14-day training program in the performing arts could reduce implicit biases. We asked healthy participants to complete an Implicit Association Test (IAT) to assess biased attitudes to physical illness in two separate sessions, before and after the training program. Two separate control groups matched by age, gender and educational level completed the two IAT sessions, separated by same number of days, without being involved in the training program. Results showed that participants who were involved in the training program reduced their implicit bias towards illness measured through IAT in the second session. This reduction in IAT measures was not observed in the control samples, despite the two IAT measures being matched in temporal delay with the experimental group. These findings suggest that an interventional program based on the performing arts could be effective in reducing levels of implicit biases among the general population.